Clinical features of allergic rhinitis and skin prick test analysis based on the ARIA classification: a preliminary study in Malaysia - Asha'ari, Zamzil Amin; Yusof, Suhaimi; Ismail, Rushdan; Che Hussin, Che Maraina (Academy of Medicine, Singapore, 2010)
Introduction: Allergic rhinitis (AR) is a prevalent disease worldwide but is still underdiagnosed in many parts of Asia. We studied the clinical profiles of AR patients in our community based on the new ARIA classification and investigated the aetiological allergens using a skin prick test. Materials and Methods: In 2008, 142 newly diagnosed patients with AR were seen and underwent skin prick testing with 90 patients completing the study. Results: Intermittent mild and moderate/severe AR were evident in 10% and 21.1% of the patients, while persistent mild and moderate/severe were seen in 20% and 48.9%, respectively. Rhinitis and asthma co-morbidity occurred in 28.8% with asthma incidence significantly higher in persistent AR (P = 0.002). There was no significant association between AR severity, city living and asthma co-morbidity. Nasal itchiness and sneezing were the main presenting complaints and were more common in intermittent AR (P <0.05). Sleep disturbance was associated with moderate-severe AR (P <0.05). Polypoidal mucosa was associated with asthma co-morbidity (P <0.05). Monosensitivity reaction occurred in 12.2% of patients and was associated with fungi sensitivity (P <0.05). Majority of patients were oligosensitive (52.8%) and polysensitive (34.4%) and were significantly associated with moderate-severe persistent AR (P <0.01). The highest positive skin prick reaction and the largest average wheal diameter were for the house dust mites and cat allergen (P <0.05). Conclusion: Our results reflected the AR profiles in our country, which was comparable with typical profiles of the neighbouring country and other Mediterranean countries with a similar temperate climate.